STRATEGI PENERAPAN EKONOMI ISLAM BERBASIS DIGITAL UNTUK MENCAPAI TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGs) - Maulana Ihsan Yusufi Suyatno; Mirna Dyah Praptitorini; Anisa Kusumawardani; Astohar Astohar; Dhian Andanarini Minar Savitri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to explore strategic digital implementations of Islamic economic principles to support the achievement of Sustainable Development Goals (SDGs). The research uses a qualitative descriptive approach through a literature review of peer-reviewed journals and policy documents, combined with an analysis of current digital platforms in Islamic finance. The findings show that digitalization in Islamic economics has the potential to improve financial inclusion, zakat and waqf management, and encourage responsible investment, thereby aligning with multiple SDG targets. The findings highlight the urgent need for synergistic collaboration among stakeholders to digitize Islamic economic instruments for broader socio-economic impact.